THE VALUE OF TEACHING THE COMBINATORY DEPARTMENT IN SCHOOL - Nabiyev Farrux Abduraximovich (Journals Park Publishing, 2022)
Mathematics has long been used to solve various life problems in the history of mankind. Simple calculations and measurements related to practical human needs have been performed. Mathematical problems, such as choosing objects and placing them in a certain order, have always been considered areas of human interest. Combinatorics is one of the main branches of mathematics, and it is important because of its relevance.
Keywords: mathematics, combinatorics, associations.